Structure Design and Analysis of A Hexapod Mechanism Walking Leg - Zhang Jiulei (Jixie chuandong)
Based on the crank link mechanism and hydraulic drive,a hexapod walking mechanism is designed and developed. The walking leg mechanism is analyzed and its mechanics model is built. The kinematics and dynamics of this walking leg are analyzed,and the devices of the hydraulic system for walking mechanism are calculated and selected. The motion relationship between hexapod walking mechanism and walking leg is determined,a reference value for in- depth research and design of gait planning and control system in hexapod robot is provided.